Exploring phenotypic diversity and stability of key traits for apple breeding in northeastern Spanish germplasm - Bielsa, Francisco Javier; Errea, Pilar; Iturmendi, Nerea; Irisarri, Patricia; Navarro, Montserrat; Castel, Lourdes; Urrestarazu, Jorge; Santesteban, Luis Gonzaga; Miranda, Carlos; Pina, Ana (Frontiers in Plant Science, 2025)
Malus x domestica Borkh is a key temperate fruit crop globally, but climate change and market demands highlight the need to broaden its narrow genetic base. The collection and conservation of local germplasms support breeding efforts by enabling the development of resilient phenotypes with improved traits. Under this framework, a set of 130 apple accessions (recovered from Northeastern Spain and 14 commercial cultivars were analyzed in terms of 12 phenotypic traits (firmness, SSC, malic acid, enzymatic browning (EB) susceptibility, fructose and glucose content, and phenolic content in peel and pulp). A statistical framework was developed to assess trait stability under shifting climatic conditions and detect significant correlations between climatic variables and phenotypical performance of apple trees. The results revealed a wide phenotypical variation across the studied traits, with the distribution of physicochemical traits strongly influenced in a genotype-dependent manner. A correlation matrix was obtained for studied traits revealing positive correlations between harvest date and SSC, enzymatic browning and firmness. Furthermore, uni- and multifactorial ANOVA revealed that genetic group (GG) is a key factor influencing all measured traits, especially pH, SSC, EB, and browning speed. Several interaction effects were also statistically significant, especially those involving ploidy level, which strongly influenced malic acid content and EB responses. Additionally, significant differences in fructose content were observed depending on peel coloration, and year-to-year phenotypic variation appeared to be predominantly governed by genotypic response to environmental conditions. Moreover, obtention of a mean stability index (Di) for each trait allowed the identification of ‘Pinova’,’Fuji’ and ‘Gala’ as the most stable cultivars among 11 commercial cultivars. These findings will support future research on development of functional cultivars and selection of ideal genotypes under shifting conditions.